AKTIVITAS ANTIOKSIDAN SENYAWA GOLONGAN FLAVONOID EKSTRAK ETANOL DAGING BUAH TERONG BELANDA (Solanum betaceum Cav.) - Raka Astiti Asih, Ida Ayu; Sudiarta, I Wayan; Wulan Suci, Ade Ayu (Jurnal Kimia (Journal of Chemistry); Vol. 9, no. 1 Januari 2015, 2015)
Terong belanda ( Solanum betaceum Cav.) is a good nutrient for health because of its potential as anti-oxidant. Anti-oxidants work by giving one of its electrons to the compounds that are oxidants so that its activity can be inhibited. Extraction was done by maceration and partition, separation and purification with chromatography analysis, identification of active compound using UV-Vis and FTIR spectrophotometer and testing of anti-oxidant activity with diphenylpicrylhydrazyl (DPPH) method. Extraction of 3,950 grams of fresh terong belanda flesh using 5L 70% ethanol produced 178,44 grams ethanol extract. Partition of 100 g ethanol extract gained three concentrated extracts in n-hexane (0.45 g), chloroform (0.37 g) and n-buthanol (3.39 g). The phytochemical test showed that n-buthanol extract contained flavonoids compounds. The result of anti-oxidant activity was showed that ethanol extract and n-buthanol extract had IC 50 of  1,302.08 ppm and 606.06 ppm. Column chromatography analysis on n-buthanol extract with mobile phase n-buthanol:ethyl acetate:10% acetic acid (2:7:1) resulted in 7 fractions (F1, F2, F3, F4, F5, F6, F7) and phytochemical test showed that fraction F2 belonged to flavonoids compound. Infrared analysis identified that isolate had –OH, C=O, C-O, C=C aromatic, CH aromatic, and CH aliphatic. Isolate analysis using UV-Visible gained 2 peaks at ? 322 nm (band I) and ? 285 nm (band II) which indicated that the flavonoids groups was flavanone or dihydroflavonol. By using “shifting” reagent the isolate was suggested to contain flavanone group with hyrdoxy groups at C-2’, C-5’, C-6’ and O-glycoside group at C-7 atom.
Keywords: anti-oxidant, flavonoids, Solanum betaceum Cav., diphenylpicrylhydrazyl